New Lithium Bis(trifluoromethanesulfonyl)imide Electrolytes Based on Rice Starch - Uribe, Ramiro; Delgado Rosero, Miguel Iban; Jurado Meneses, Nori Magali (Revista Científica, 2026)
In this work, biopolymer electrolyte membranes based on rice starch and CF3SO2NLiSO2CF3 (LiTFSI) were prepared via the solution casting method and characterized by impedance spectroscopy (IS), differential scanning calorimetry (DSC), and cyclic voltammetry (CV). The graphs of the ionic conductivity logarithm as a function of the inverse of the temperature exhibit an Arrhenius behavior, which indicates a thermally activated conduction process, while the DSC results reveal a step-shaped anomaly associated with the glass transition temperature (Tg) of a new polymer complex. The cyclic voltammetry analysis suggests a qualitative electrochemical stability range between -2.5 and +2.5 V. At room temperature, the highest ionic conductivity obtained was higher than 9 × 10⁻³ S·cm⁻¹ for the membrane containing 50 wt.% LiTFSI. Despite the notable enhancement in ionic conductivity, membranes with higher salt content exhibit reduced mechanical robustness and may be affected by residual moisture. These findings highlight the potential of rice starch-LiTFSI systems as promising candidates for future electrochemical devices, although further optimizations are required, such as mechanical reinforcement and more detailed stability assessments for practical implementation.